2016
DOI: 10.1136/bmjopen-2015-009044
|View full text |Cite
|
Sign up to set email alerts
|

Models of antenatal care to reduce and prevent preterm birth: a systematic review and meta-analysis

Abstract: ObjectiveTo assess the effectiveness of models of antenatal care designed to prevent and reduce preterm birth (PTB) in pregnant women.MethodsWe conducted a search of seven electronic databases and reference lists of retrieved studies to identify trials from inception up to July 2014 where pregnant women, regardless of risk factors for pregnancy complications, were randomly allocated to receive an alternative model of antenatal care or routine care. We pooled risks of PTB to determine the effect of alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…Fernandez Turienzo et al (2016), in their systematic review and meta-analysis of models of antenatal care designed to reduce and prevent preterm birth, found that while "alternative" models of care (i.e. midwife-led continuity of care and specialised care) reduce preterm birth compared to standard care, conclusions on the relative benefits of the two models could not be drawn.…”
Section: Aspects Of Care and Interactions With Professionalsmentioning
confidence: 99%
“…Fernandez Turienzo et al (2016), in their systematic review and meta-analysis of models of antenatal care designed to reduce and prevent preterm birth, found that while "alternative" models of care (i.e. midwife-led continuity of care and specialised care) reduce preterm birth compared to standard care, conclusions on the relative benefits of the two models could not be drawn.…”
Section: Aspects Of Care and Interactions With Professionalsmentioning
confidence: 99%
“…Modifying the risk and protective factors inherent in adolescents daily lives, especially for those who are most socio-economically disadvantaged, can improve health outcomes (Viner et al, 2012). Indeed, programmes targeted to improve the circumstances of socially disadvantaged women can reduce PTB (Fernandez Turienzo et al, 2016;Hollowell et al, 2011). While there is some evidence that single interventions including smoking cessation, improved diet for under-nourished women, and antenatal lower genital tract screening are effective in reducing PTB rates (Piso et al, 2014); the effect of model of care is a PTB research priority (Duley et al, 2014).…”
Section: Preterm Birthmentioning
confidence: 99%
“…Antenatal care is generally thought to improve pregnancy outcomes including preterm birth (Fernandez Turienzo et al, 2016;Hollowell et al, 2011). Receiving less than five visits, compared to five or more visits, has been associated with an eightfold increase in preterm birth, after adjusting for known confounders (Raatikainen et al, 2007).…”
Section: More Frequent Antenatal Visitsmentioning
confidence: 99%
“…The sample size calculation assumed and estimated that 20% of the individuals in the poorest quintile do not receive more than two antenatal care visits and are less likely to deliver by a skilled birth attendant in Cameroon [2][3][4][5][6][7][8]. Previous studies reported an approximately 10-15% increase in the use of antenatal care and a 10% increase in the use of skilled delivery [18][19][20][21][22][23][24][25][26]. Thus, the study assumes a 15% difference compared with the control assuming an inter-cluster coefficient of 0.001 [26,45,46], with four clusters.…”
Section: Sample Sizementioning
confidence: 99%
“…In Africa, most women are unable to seek health care due to high out-of-pocket costs [1][2][3][4][5][6][7][8][9][10][11][12]. Systematic reviews on voucher interventions in addressing maternal mortality have shown that vouchers can be effective in improving access to and utilization of maternal health services, especially in poor and underserved communities [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Vouchers typically grant purchasing power to low-income individuals who may otherwise be ignored in the market due to their lack of funds or knowledge of goods and services [18,19].…”
Section: Introductionmentioning
confidence: 99%